Application of MODIS images for modelling the energy balance components in the semi-arid conditions of Brazil - Teixeira, Antonio H. de C.; Scherer-Warren, Morris; Lopes, Helio L.; Hernandez, Fernando B. T. [UNESP]; Andrade, Ricardo G.; Neale, Christopher M. U.; Neale, CMU; Maltese, A. (Spie-int Soc Optical Engineering, 2013)
In the semi-arid areas of Petrolina municipality, Northeast Brazil, irrigated agriculture has replaced the natural vegetation, thus the quantification of the energy exchanges between the plants and the low atmosphere is important. MODIS satellite images and agro-meteorological data for the years of 2010 and 2011 were used together, for modelling the energy balance components under these conditions. Surface albedo (alpha(0)), NDVI and surface temperature (T-0) were the remote sensing parameters required to calculate the latent heat flux (lambda E) and the surface resistance to evapotranspiration (r(s)) on a large scale. The daily net radiation (R-n) was retrieved from alpha(0), air temperature (T-a) and transmissivity (tau(sw)), allowing the quantification of the sensible heat flux (H) by residual in the energy balance. With threshold values for r(s), it was possible to do a simplified vegetation classification. The incident solar radiation (RS down arrow) partitioned as R-n ranged from 0.40 to 0.51, corresponding respectively to periods after the rainy season and the driest conditions of the year, with the observed differences between irrigated crops and natural ecosystem not significant. Considering all periods along the year, the averaged fractions of R-n partitioned as H, were 31 and 78%, for irrigated crops and natural vegetation, respectively, while as lambda E the corresponding ratios were 69 and 22%. Heat advection from the dry areas surrounding irrigated plots was observed with lambda E exceeding R-n by 9% during the coldest periods. The models tested herein can be used for monitoring the energy exchanges in agro-ecosystems under conditions of land use and climate change.
Keywords: surface albedo; surface temperature; NDVI; latent heat flux; sensible heat flux